The INFLUENCE OF FINANCIAL LITERACY, FINANCIAL SOLVENCY, AND RISK TOLERANCE ON FINANCIAL SATISFACTION OF GENERATION Z, JAMBI CITY - Aryajati, Djodi; Setiawati, Rike; Solikhin, Agus (Journal of Business Studies and Management Review, 2024)
A person's life satisfaction will also be determined by the current financial condition he or she has or what is more often called financial satisfaction. This research aims to determine the influence of Financial Literacy, Financial Solvency, and Risk Tolerance on the Financial Satisfaction of Generation Z in Jambi City. This research is quantitative in nature and the research data used is primary data. The population used is Generation Z over 20 years old and already have their own income, amounting to 103,144 people. Sampling used the Slovin formula with a percentage of 10% with a total of 100 respondents. Data collection was carried out through validity and reliability tests, R-Square tests and hypothesis testing with bootstrapping using SmartPLS 3.0 software. The research results show that Financial Literacy, Financial Solvency, and Risk Tolerance have a positive and significant effect on Financial Satisfaction.